Comprehensive behavioral analysis of pituitary adenylate cyclase-activating polypeptide (PACAP) knockout mice - Hattori, Satoko; Takao, Keizo; Tanda, Koichi; Toyama, Keiko; Shintani, Norihito; Baba, Akemichi; Hashimoto, Hitoshi; Miyakawa, Tsuyoshi (Frontiers in Behavioral Neuroscience, 2012)
Pituitary adenylate cyclase-activating polypeptide (PACAP) is a neuropeptide acting as a neurotransmitter, neuromodulator, or neurotrophic factor. PACAP is widely expressed throughout the brain and exerts its functions through the PACAP-specific receptor (PAC1). Recent studies reveal that genetic variants of the PACAP and PAC1 genes are associated with mental disorders, and several behavioral abnormalities of PACAP knockout (KO) mice are reported. However, an insufficient number of backcrosses was made using PACAP KO mice on the C57BL/6J background due to their postnatal mortality. To elucidate the effects of PACAP on neuropsychiatric function, the PACAP gene was knocked out in F1 hybrid mice (C57BL/6J x 129SvEv) for appropriate control of the genetic background. The PACAP KO mice were then subjected to a behavioral test battery. PACAP deficiency had no significant effects on neurological screen. As shown previously, the mice exhibited significantly increased locomotor activity in a novel environment and abnormal anxiety-like behavior, while no obvious differences between genotypes were shown in home cage activity. In contrast to previous reports, the PACAP KO mice showed normal prepulse inhibition and slightly decreased depression-like behavior. Previous study demonstrates that the social interaction in a resident-intruder test was decreased in PACAP KO mice. On the other hand, we showed that PACAP KO mice exhibited increased social interaction in Crawley’s three-chamber social approach test, although PACAP KO had no significant impact on social interaction in a home cage. PACAP KO mice also exhibited mild performance deficit in working memory in an eight-arm radial maze and the T-maze, while they did not show any significant abnormalities in the left-right discrimination task in the T-maze. These results suggest that PACAP has an important role in the regulation of locomotor activity, social behavior, anxiety-like behavior and, potentially, working memory.